Analysis of three works for clarinet, viola and piano by liduino pitombeira (2019)
A search for Latin American repertoire for the instrumental ensemble of clarinet, viola and piano has revelated the lack of information and the need for more in-depth study on this topic (Correa Suárez & Sheldrick, 2019). This article discusses three works by the Brazilian composer Liduino Pitombeira and includes a formal analysis as well as an examination of the use of the instruments throughout the works.